how do you solve this ???

The first thing you do is multiply the right side out. So, x(x^{2 }- 8x + 5x - 40) -> x(x^{2 }- 3x - 40) -> x^{3
}- 3x^{2} - 40x

So y = x^{3} - 3x^{2} - 40x

how do you solve this ???

Tutors, please sign in to answer this question.

The first thing you do is multiply the right side out. So, x(x^{2 }- 8x + 5x - 40) -> x(x^{2 }- 3x - 40) -> x^{3
}- 3x^{2} - 40x

So y = x^{3} - 3x^{2} - 40x

Rachel K.

Princeton '13 Math Tutor

New York, NY

5.0
(30 ratings)

Louis I.

Computer Science, Design & Programming, and English Writing Skills

Staten Island, NY

5.0
(101 ratings)

## Comments

thank you(: